Evolusi Sel Sebagai Dasar Perkembangan Makhluk Hidup Saat ini - Lukman, Aprizal (Universitas Jambi, 2008)
Understanding the cell biology evolution theory is very important in studying recent creature developmentlately. Basically, creature evolution theories argue that animal, plant as well as human has been well developing fromvery simple forms. So far, Cell has been treated as unique structural and functional unit. Cell is also the smallestcreature heredity unit